Application of a weather simulation model based on observed daily meteorological data in humid tropical climate - Chineke, T.C.; Jagtap, S.S.; Aina, J.I. (Springer, 1999)
Long time series of daily meteorological data that are needed in various applications are not always available or appropriate for use at many locations. The Weather Generation Model (WGEN) developed by Richardson and Wright (1984) was evaluated as a substitute for daily observed data at 17 sites located in the main climatic zones of Nigeria. The Wilcoxon-Mann-Whitney U-test has shown that the number of months per year, for which the differences between the long-term monthly mean observed meteorological and WGEN simulated data, were signi®- cant, was less than 4 at most of the study sites.